Versatility of the Angularis Oris Axial Pattern Flap for Facial Reconstruction. Issue 8 (17th October 2015) - Losinski, Sara L.; Stanley, Bryden J.; Schallberger, Sandra P.; Nelson, Laura L.; Millard, Heather A.M. Towle
Abstract : Objective: To describe the versatility of the axial pattern flap based on the cutaneous perforating branch of the angularis oris artery for reconstruction of large facial defects in dogs, including complications and clinical outcomes. Study Design: Retrospective clinical case series. Animals: Client‐owned dogs (n = 8). Methods: Facial flaps (n = 9) based at the commissure of the lip with a caudodorsal orientation were utilized, with established anatomical borders. Flaps were elevated deep to the panniculus carnosus in a caudal to rostral direction, preserving the angularis oris artery, its cutaneous perforator, and surrounding cutaneous vasculature. Flaps were rotated dorsally or ventrally to cover the defect. Primary closure of the donor site was by direct apposition in all cases. Results: Angularis oris axial pattern flaps were most commonly used to close large defects of the nasomaxillary area rostral to the eyes (6 dogs), followed by orbital (2) and intermandibular (1) defects. Defects occurred because of tumor resection (6 dogs), trauma (2), and a chronic, non‐healing wounding (1). All flaps healed with acceptable functional and cosmetic outcomes without major complications. Followup ranged from 10 days to 16 months. Minor postoperative complications included flap edema (8 dogs), partial incisional dehiscence (3), distal tip necrosis (2), and oroantral fistula recurrence (1). Conclusion: Angularis oris axial pattern flaps provided hirsute, full‐thickness skin coverage of a variety of large facial defects with minor complications, and should be considered when restructuring large defects of the rostral face or chin.